The Effect of Anise and Rosemary on Broiler Performance - Al-Kassie, Ghalib Alwan Mohammed (International Journal of Poultry Science, 2008)
The present study was conducted to explore the usage of different level of Anise and Rosemary in broiler nutrition as a natural growth promotion. Different levels were added to a standard diet, to determine its effect on the daily feed intake, daily live weight and feed conversion ratio compared to a control group. Two hundred fifty day-old broilers(Arbor Acre)were divided into five equal groups as follows, Control group (no addition of Anise and Rosemary), Anise 0.5%, Anise 1%, Rosemary 0.5% and rosemary 1%. The experiment carried out in 42 days. The feed intake was significantly (P